INCLUSION OF PROPOLIS IN RABBIT DIETS AND SEMEN CHARACTERISTICS - Moraes, Gentil Vanini de; Mataveli, Marcela; Moura, Lucimar Pontara Peres de; Scapinello, Cláudio; Mora, Freddy; Osmari, Milene Puntel (Arquivos de Ciências Veterinárias e Zoologia da UNIPAR, 2015)
This experiment was carried out with the objective of evaluating different levels of powder propolis in rabbit diets and their effect on semen characteristics. A total of 36 New Zealand White male rabbits were used, randomly distributed into six groups, corresponding to six propolis levels (0, 0.25, 0.50, 0.75, 1.0 and 1.25 g propolis/kg of ration). Semen was collected twice a week, using an artificial vagina. Semen volume, progressive spermatic motility, spermatic vigor, spermatic concentration and spermatic morphology were analyzed. General linear models were used for statistical analysis. The inclusion of powder propolis in the diet increased normal spermatozoa percentage and reduced spermatozoa abnormalities. The powder propolis did not affect the progressive spermatic motility, spermatic vigor or spermatic concentration. The values were considered normal for rabbits. However, a small reduction in semen volume was observed, without any negative effect on the other semen characteristics evaluated. Thus, it is possible to observe better semen quality with the inclusion of 1.25 g powder propolis/kg in the diet for reproducer rabbits.